Chirality as a tool for function in porous organic cages - Hasell,T; Little,MA; Chong,SY; Schmidtmann,M; Briggs,ME; Santolini,V; Jelfs,KE; Cooper,AI (Nanoscale, 2017)
The control of solid state assembly for porous organic cages is more challenging than for extended frameworks, such as metal–organic frameworks. Chiral recognition is one approach to achieving this control. Here we investigate chiral analogues of cages that were previously studied as racemates. We show that chiral cages can be produced directly from chiral precursors or by separating racemic cages by co-crystallisation with a second chiral cage, opening up a route to producing chiral cages from achiral precursors. These chiral cages can be cocrystallized in a modular, ‘isoreticular’ fashion, thus modifying porosity, although some chiral pairings require a specific solvent to direct the crystal into the desired packing mode. Certain cages are shown to interconvert chirality in solution, and the steric factors governing this behavior are explored both by experiment and by computational modelling.